Credit Union Sauan Sibarrung sebagai Ruang Perjumpaan dalam Membangun Persaudaraan Ekumenis Antar Umat Katolik dan Berbagai Gereja Kristen di Toraja - Yohanes Subali; Huliandro Di’Almon Pan; Benediktus Tangke Allo (Jurnal Penelitian Pendidikan Agama Katolik, 2026)
This study aims to understand how the Sauan Sibarrung Credit Union serves as a space of encounter that strengthens fraternal relationships between Catholics and various Christian churches in Toraja. The research focuses on the concrete experiences of members as they engage in the dynamics of dialogue of life through the socio-economic activities they carry out together. A descriptive qualitative approach was employed using the Interpretative Phenomenological Analysis (IPA) method, involving 138 respondents who provided answers through questionnaires and guided interviews. This was complemented by a literature review of relevant Church documents and previous studies. The findings show that the Sauan Sibarrung Credit Union is perceived as an inclusive institution that embraces ecclesial diversity and facilitates cooperation that fosters trust, solidarity, and mutual respect among its members. Torajan cultural values, such as the spirit of sharing, communal kinship, and faithfulness, form an essential foundation in creating an atmosphere of togetherness across different churches. These shared economic practices, member education, and community development activities not only support social empowerment but also embody a form of grassroots ecumenism that grows organically from daily encounters. This study demonstrates that the Sauan Sibarrung Credit Union can be understood as a model of ecumenical praxis that integrates local cultural life, Christian spirituality, and concrete social collaboration.